Measuring Corporate Financial Stability and Growth: Empirical Evidence from Vertical and Horizontal Analysis - Anastasia, Jeniffer; Deary, Rizvan; Wijayanti, Elok Dwi; Adam, Alfin; Khohari, Melyana; Sharon, Salmah (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2025)
Purpose: To analyze the growth direction and stability of PT Bersama Mencapai Puncak Tbk's financial performance for the 2020–2022 period. Method: A quantitative approach using financial ratio analysis and horizontal and vertical analysis of the company's secondary financial statements. Results: : A quantitative approach using financial ratio analysis and horizontal and vertical analysis of the company's secondary financial statements. Novelty: The novelty of this research lies in the integration of horizontal and vertical analysis in a post-pandemic context. Contribution: Theoretically supports cost efficiency and budget control, and practically provides guidance for improving the company's financial structure and profitability Abstrak: Mengukur Stabilitas dan Pertumbuhan Keuangan Perusahaan: Bukti Empiris dari Analisis Vertikal dan Horizontal Tujuan: Menganalisis pertumbuhan dan stabilitas kinerja keuangan PT. Bersama Mencapai Puncak Tbk periode 2020–2022. Metode: Pendekatan kuantitatif melalui analisis rasio keuangan serta analisis horizontal dan vertikal terhadap laporan keuangan sekunder perusahaan  Hasil: Pendekatan kuantitatif melalui analisis rasio keuangan serta analisis horizontal dan vertikal terhadap laporan keuangan sekunder perusahaan  Kebaruan: Kebaruan penelitian terletak pada integrasi analisis horizontal dan vertikal dalam konteks pasca-pandemi. Kontribusi: Mendukung efisiensi biaya dan pengendalian anggaran, serta secara praktis memberi arahan perbaikan struktur keuangan dan profitabilitas perusahaan.